Synthesis of BiFeO3/ZnO heterojunction with enhanced piezocatalytic performance for highly-effective degradation of organic pollutant - Yao Feng; Jinhua Li; Hao Yan (Journal of Advanced Dielectrics)
In this work, a series of BiFeO3/ZnO composites with varying molar ratio of BiFeO3 to ZnO (Bi:Zn = 2.5:1, 5:1, 10:1, 20:1) have been synthesized via a one-step hydrothermal method and evaluated for their efficiency in rhodamine B (RhB) degradation performance. The morphology results reveal that the microsphere-shaped ZnO is dispersed on the surface of the blocky-like BiFeO3, with intimate contact between the two phases. It has been found that the maximum piezocatalytic activity could be achieved at BiFeO3/ZnO molar ratio of 5:1, with a degradation rate up to 92% for RhB. Compared with pure BiFeO3 and ZnO, the composites have superior piezocatalytic degradation performance. The reason for the enhanced piezocatalytic dye degradation rate may be that the BiFeO3/ZnO composites effectively separate the positive and negative charges to reduce the recombination of positive and negative charges. These active species, such as superoxide radicals ([Formula: see text]) in the process of piezocatalytic, are proved on the active species capture experiments. The BiFeO3/ZnO composites have good piezocatalytic degradation performance, which provides an option for collecting vibration energy to degradation dye wastewater in the future.